Allicin Facilitates Airway Surface Liquid Hydration by Activation of CFTR - Qiu, Zhuo-Er; Xu, Jian-Bang; Chen, Lei; Huang, Ze-Xin; Lei, Tian-Lun; Huang, Zi-Yang; Hou, Xiao-Chun; Yang, Hai-Long; Lin, Qin-Hua; Zhu, Yun-Xin; Zhao, Lei; Zhou, Wen-Liang; et al. (Frontiers in Pharmacology, 2022)
Airway epithelium plays critical roles in regulating airway surface liquid (ASL), the alteration of which causes mucus stasis symptoms. Allicin is a compound released from garlic and harbors the capacity of lung-protection. However, the potential regulatory effects of allicin on airway epithelium remain elusive. This study aimed to investigate the effects of allicin on ion transport across airway epithelium and evaluate its potential as an expectorant. Application of allicin induced Cl− secretion across airway epithelium in a concentration-dependent manner. Blockade of cystic fibrosis transmembrane conductance regulator (CFTR) or inhibition of adenylate cyclase-cAMP signaling pathway attenuated allicin-induced Cl− secretion in airway epithelial cells. The in vivo study showed that inhaled allicin significantly increased the ASL secretion in mice. These results suggest that allicin induces Cl− and fluid secretion across airway epithelium via activation of CFTR, which might provide therapeutic strategies for the treatment of chronic pulmonary diseases associated with ASL dehydration.